Pharmacovigilance quality system for vaccine monitoring (COVID-19) using quality indicators: a scoping review - de Oliveira, Mayra M. Moura; Wagner, Gabriela Arantes; Gattás, Vera L.; Arruda, Larissa de Souza; Taminato, Monica (International Journal of Infection Control, 2021)
This scoping review responds to the appeal of the scientific community for collaboration between different entities for pharmacovigilance and active surveillance of coronavirus disease 2019 (COVID-19) vaccines. The objective is to identify, systematically evaluate, and synthesize the best scientific evidence available on the indicators used in pharmacovigilance systems. Our results demonstrate that approximately 50% of the 25 studies used in this review have been carried out in the past 5 years. Of these, only four used the pharmacovigilance indicators proposed by the World Health Organization (WHO). Eighty-seven pharmacovigilance indicators were identified, of which seven (8.0%) related to signal detection. While the WHO advocates signal detection as routine pharmacovigilance, in special situations – such as accelerated clinical studies where adverse events are not yet well known – other indicators related to signal detection appear to be good options for maintaining quality pharmacovigilance and active surveillance in the development of the COVID-19 vaccine. However, the less robust pharmacovigilance systems in low-income countries will necessitate greater involvement of health professionals from public and private sectors, pharmaceutical companies, academic institutions, and the general public, to ensure information security and detection of signals for the COVID-19 vaccine.